Sclera color in humans facilitates gaze perception during daytime and nighttime. - Jessica L Yorzinski; Amy Harbourne; William Thompson (PLoS ONE, 2021)
Species vary widely in the conspicuousness of their eye morphology and this could influence gaze perception. Eyes with conspicuous morphology can enhance gaze perception while eyes with camouflaged morphology may hinder gaze perception. While evidence suggests that conspicuous eye morphology enhances gaze perception, little is known about how environmental conditions affect this interaction. Thus, we investigated whether environmental light conditions affect gaze perception. Human subjects (Homo sapiens) were instructed to find direct-gaze faces within arrays of averted-gaze faces or to find averted-gaze faces within arrays of directed-gaze faces. The faces were displayed under conditions simulating nighttime or daytime conditions. Furthermore, the faces had naturally-colored sclera (white) or modified sclera (same color as the iris). Participants were fastest and most accurate in detecting faces during the daytime and nighttime conditions when the sclera were naturally-colored. Participants were worst at detecting faces with modified sclera during the nighttime conditions. These results suggest that eyes with conspicuous morphology enhance gaze perception during both daytime and nighttime conditions.